2000
DOI: 10.1034/j.1600-0714.2000.290604.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hepatitis C virus RNA in oral lichen planus and oral cancer tissues

Abstract: Hepatitis C virus (HCV) infection not only causes chronic liver diseases but shows extrahepatic manifestations as oral lichen planus (OLP) and oral cancer. To elucidate the direct relationships among these diseases and HCV infection, we investigated the detection of positive- and negative-strand HCV-RNA from serum, OLP (n=19), and oral cancer (n=17) tissues. We used a sensitive reverse transcription to polymerase chain reaction (RT-PCR) method, and analyzed sequences from the HCV El/E2 region of the genome fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
86
0
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 35 publications
(43 reference statements)
2
86
0
7
Order By: Relevance
“…Pilli et al [96] detected HCV-specific T cells with phenotypic and functional characteristics of terminally differentiated effector cells at the site of the oral lesions. These findings and the detection of HCV RNA strands in the lichen tissue [97] suggests a possible role for HCVspecific T-cell responses in the pathogenesis of lichen planus associated with HCV infection [98] . Our study has demonstrated a high prevalence of extrahepatic manifestations in Bulgarian patients with chronic HCV infection.…”
Section: Discussionmentioning
confidence: 80%
“…Pilli et al [96] detected HCV-specific T cells with phenotypic and functional characteristics of terminally differentiated effector cells at the site of the oral lesions. These findings and the detection of HCV RNA strands in the lichen tissue [97] suggests a possible role for HCVspecific T-cell responses in the pathogenesis of lichen planus associated with HCV infection [98] . Our study has demonstrated a high prevalence of extrahepatic manifestations in Bulgarian patients with chronic HCV infection.…”
Section: Discussionmentioning
confidence: 80%
“…The rate of malignant transformation of these lesions is 3-20% (42). Furthermore, our study suggests the presence and elevation of HCV RNA in oral cancer and OLP tissues (43). Multi-center studies in Japan found that the presence of anti-HCV and HCV RNA was significantly higher in patients with squamous cell carcinoma of the head and neck than in control subjects (14).…”
Section: Discussionmentioning
confidence: 91%
“…Samples positive for HCV-RNA were detected in tissues of oral cancer (19) and OLP (20). Some of HCV proteins, called "the core" and "the non-structural 3 protein", can accelerate the cell cycle in vitro (21,22).…”
Section: Discussionmentioning
confidence: 99%